Hjulstabron (Hjulsta bridge), Sweden. Issue 3 (16th September 2019) - Top, Reinald; ten Wolde, Leo; Visser, Wouter
ABSTRACT: In Sweden, the existing Hjulsta bridge that connects Norrköping to Uppsala via the Highway 55 needs to be replaced by a new bridgeas shown in Fig. 1 . ZJA Zwarts & Jansma Architects, together with Bosch Slabbers Landscape + Urban Design (landscape architects) and Iv‐Consult (engineering consultancy) formed a Dutch design and engineering team that collaborated with NRC Infrapro and the Swedish Transport Administration to formulate the specifics of the bridge. The subsequent concept design brought all requirements together, resulting in a beautiful slender steel bridge both with regards to the fixed deck as well as the moveable part.